Kazi Nazrul Islam : a biography - Goswami, Karuṇamaya, 1943- (Dhaka, Bangladesh : Nazrul Institute, 1996)
On Kazi Nazrul Islam, 1899-1976, Bengali poet of India and Bangladesh.
"Books of Kazi Nazrul Islam": P. 173-178.
Keywords: Nazrul Islam, -- Kazi, -- 1899-1976.; Poets, Bengali -- 20th century -- India -- Biography; Poets, Bengali -- 20th century -- Bangladesh -- Biography